Stories From 55 Years of a Transatlantic Friendship. Geschichten aus 55 Jahren transatlantischer Freundschaft/Smith College & Universität Hamburg 1961 - 2016 - Nicolaysen, Rainer; Kolb, Jocelyne (Hamburg University Press, 2017)
The origin of this story of origins is the celebration, in June 2011, that took place in Hamburg to mark the fiftieth anniversary of the Smith College Junior Year Program at the University of Hamburg. We wanted to replicate in print what we witnessed in person: the voicing of vivid memories that were never identical but invariably familiar; the effortless manner in which people from two institutions and two countries met and mingled; the wisdom and wit with which participants reflected on the profound effect of studying and teaching thousands of miles away from home. We wanted a record of how this remarkable program came into being and of how people over the decades have responded to and remembered what is an exchange in the truest sense. The ease with which we were able to collect some 40 contributions testifies to the strong ties between Smith College and the University of Hamburg - between Northampton and Hamburg. The essays in this volume capture the regular and lively talk between our institutions and cities.